2019
DOI: 10.1136/thoraxjnl-2018-212665
|View full text |Cite
|
Sign up to set email alerts
|

12-month randomised controlled trial of ginseng extract for moderate COPD

Abstract: Background Panax ginseng (ginseng) is a therapeutic herb which might be beneficial in COPD. The study investigated if ginseng, compared with placebo, is effective and safe for people with moderate COPD.MethodsThis multicentre, randomised, double-blind, placebo-controlled trial compared 24 weeks of ginseng capsules (100 mg twice daily) with placebo. Participants were followed up for a further 24 weeks. Participants were aged 40 years and over and had airflow limitation in the moderate (Global Initiative for Chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The main results of this study are similar to our previous clinical trial of Panax ginseng for moderate COPD. 22 In the previous study, ginseng was administered at a lower dose in people with more moderate COPD, and quality of life was the primary outcome. Therefore, this is the first randomized, double-blind, placebo-controlled clinical trial evaluating the efficacy and safety of standardized Panax ginseng extract for moderate to very severe stable COPD.…”
Section: Discussionmentioning
confidence: 99%
“…The main results of this study are similar to our previous clinical trial of Panax ginseng for moderate COPD. 22 In the previous study, ginseng was administered at a lower dose in people with more moderate COPD, and quality of life was the primary outcome. Therefore, this is the first randomized, double-blind, placebo-controlled clinical trial evaluating the efficacy and safety of standardized Panax ginseng extract for moderate to very severe stable COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Panax ginseng is a therapeutic herb with potential benefits for patients with COPD (13). Recently, Shergis et al (14) reported results from a 12-month randomized controlled trial of ginseng extract for treatment of moderate COPD. The primary endpoints of their study were scores on the St George's Respiratory Questionnaire (15), the COPD Assessment Test (16) and the Short Form Health Survey (17).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first case report showing long-term maintenance of body weight and nutritional status with ninjinyoueito in terminal patients with chronic respiratory diseases. Ninjinyoueito is becoming an increasingly commonly prescribed medication for patients with chronic respiratory disease such as COPD (3,14,18). Although the underlying mechanism by which ninjinyoueito counteracts weight loss and induces maintenance of nutritional status remains unclear, this Kampo medicine may be used as a supplementary treatment for terminal patients with respiratory diseases.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 Multiple centers involved in randomized controlled trials have explored the clinical effects of the Chinese herbal formula, Yu Ping Feng granules and the single herb Ginseng for the treatment of COPD. 19 , 20 The medical effects of CM therapies have been validated in an increasing number of clinical trials, to satisfy the need for evidence-based medicine. In addition to the evidence of therapeutic interventions, patient beliefs and preferences are powerful influences on the treatment effects in clinical practice.…”
Section: Introductionmentioning
confidence: 99%